Komitmen Organisasional Pada Karyawan Generasi Milenial: Peran Nilai Kerja dan Kepuasan Kerja - Christian Budianto; Dhyah Harjanti; Widjojo Suprapto (Majalah Ekonomi, 2021)
ABSTRACT The increasing dominance of the millennial generation in the world of work requires organizations to understand and accommodate the characteristics and values of the millennial generation. This study examined the role of work values on organizational commitment through job satisfaction as a mediating variable in millennial generation employees. This study used a quantitative method with 166 respondents determined by using purposive sampling. Data were collected using an online questionnaire with a Likert scale and processed using partial least squares analysis techniques. The results showed that organizational commitment was significantly influenced by the work value and job satisfaction of Generation Y employees. The results also showed that job satisfaction acts as a mediating variable on the relationship between work value and organizational commitment among millennials.